The free-living nematode community structure within the Romanian circalittoral habitats (Geo-Eco-Marina, 2020)
The paper presents an asssessment of nematode community structure and diversity performed in May 2018 within two habitats of the Romanian circalittoral zone. The differences in nematodes distribution as a result of Danube’s influence are also highlighted. Tolerant species to organic enrichment dominated the population structure within the terrigenous mud habitat with Melinna palmata, while a gradual decreasing of their abundances with habitat changing to mixed sediments with Dipolydora quadrilobata and with depth increasing was recorded. In total, 28 taxa belonging to 16 families were identified, of which 16 on mud and 22 on mixed sediments, respectively. The nematode trophic structure dominated by tolerant deposit feeders (84%), similar to the Maturity index (ranged values 0.18 – 0.73), evinced an overall poor ecological quality status of both habitats, which represent over 70% of the two Natura 2000 protected areas located within the perimeter, the Delta Dunării – Marine zone and The South Lobe of Phyllophora Field of Zernov.
Keywords: Circalittoral habitats; free-living marine nematodes; ecological indices; Danube plume area